PEMANFAATAN DIGITAL MARKETING PADA PELAKU UMKM KULINER DI KECAMATAN CIBINONG - Muhammad Rifkhi (2021)
This study uses a qualitative method that aims to determine the understanding and knowledge, forms of utilization, and the impact of the application of digital marketing by culinary MSME owners in Cibinong District. Data collection techniques in this study used the method of observation, interviews and documentation. Interviews were conducted with 8 informants, 1 representative of the Bogor Regency Cooperatives and UMKM Service, 1 representative of MSME leaders in Cibinong District, 3 culinary MSME owners and their 3 customers. To prove the validity of the data in the study, the researchers used the triangulation and reference method. Furthermore, the data were analyzed by performing data reduction, data display and drawing conclusions. The results of this study indicate that culinary MSME owners in Cibinong District have fairly good knowledge and understanding of digital marketing. This is evidenced by their use of digital marketing, such as the GoFood, GrabFood, and Shopee Food mobile applications, as well as the Google My Business page. The impact felt after implementing digital marketing is to increase sales which have an impact on income and help in promotions that make their business more widely known.